2012
DOI: 10.1208/s12248-012-9429-3
|View full text |Cite
|
Sign up to set email alerts
|

The Liver X Receptor Agonist T0901317 Protects Mice from High Fat Diet-Induced Obesity and Insulin Resistance

Abstract: Abstract. The effect of activation of liver X receptor by N-(2,2,2-trifluoroethyl)-N-[4-[2,2,2-trifluoro-1-hydroxy-1(trifluoromethyl)ethyl]phenyl] benzenesulfonamide (T0901317) on high fat diet (HFD)-induced obesity and insulin resistance was examined in C57BL/6 mice. When on HFD continuously for 10 weeks, C57BL/6 mice became obese with an average body weight of 42 g, insulin resistant, and glucose intolerant. Twice weekly intraperitoneal injections of T0901317 at 50 mg/kg in animals on the same diet completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
(36 reference statements)
9
26
0
Order By: Relevance
“…Additionally, Laffitte et al also demonstrated that activation of LXR improved glucose tolerance in a murine model of diet-induced obesity and insulin resistance, mainly via coordinately modulating the expression of a set of genes involved in glucose metabolism (30). Consistent with these studies, our previous work demonstrated that activation of LXR by T0901317 protected mice from high-fat diet-induced insulin resistance and glucose intolerance but induced liver steatosis (29). Results summarized in this report showed that combined treatment with T0901317 and resveratrol synergistically decreased blood glucose in mice (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Additionally, Laffitte et al also demonstrated that activation of LXR improved glucose tolerance in a murine model of diet-induced obesity and insulin resistance, mainly via coordinately modulating the expression of a set of genes involved in glucose metabolism (30). Consistent with these studies, our previous work demonstrated that activation of LXR by T0901317 protected mice from high-fat diet-induced insulin resistance and glucose intolerance but induced liver steatosis (29). Results summarized in this report showed that combined treatment with T0901317 and resveratrol synergistically decreased blood glucose in mice (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Activation of LXR has also been considered as a strategy for treatment of diabetes because of its involvement in glucose metabolism. We have recently shown that T0901317, a LXR activator, suppresses high-fat diet-induced obesity but induces liver steatosis (29). In the current study, we demonstrate that resveratrol suppresses T0901317-induced fat accumulation in the liver (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…ACLY play a crucial role in obesity-related complications in glucose and lipid homeostasis of mice liver [9]. An animal study has shown activation of LXR protection effects in obesity induced by high-fat diet [41]. In the present study, we demonstrated for the first time that cinnamon polyphenol intake significantly reduced the expression of hepatic SREBP-1c, LXRs, ACLY, and FAS.…”
Section: Discussionsupporting
confidence: 60%
“…T0901317 was dissolved in dimethyl sulfoxide (DMSO) (50 mg/ml) and diluted (5:1) with 0.9% saline prior to injection according to prescribed protocols ( 41,(47)(48)(49). Control mice received the same solution without T0901317.…”
Section: Treatment Of Mice With Lxr Agonist T0901317mentioning
confidence: 99%